2021
DOI: 10.1093/jn/nxaa263
|View full text |Cite
|
Sign up to set email alerts
|

Glycine, a Dispensable Amino Acid, Is Conditionally Indispensable in Late Stages of Human Pregnancy

Abstract: Background Recently, we showed that there are higher protein, lysine, and phenylalanine requirements in late stages of pregnancy compared with early stages. Animal studies have suggested an increased dietary need for specific dispensable amino acids in pregnancy; whether such a need exists in human pregnancies is unknown. Objective The objective of the current study was to examine whether healthy pregnant women at midgestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Thus, even the relatively high protein intake of 1.13 g/kg/d, supplying about 3 g glycine/d, coupled with glycine from biosynthesis, is unlikely to meet biological requirements for optimal function. In concordance, an IAAO study showed that glycine intakes less than 37 mg/kg/d result in increased phenylalanine oxidation among late gestation pregnant women [ 95 ] (see next section). Arguments for glycine supplementation have also been made based on the observation that tissue glycine levels are often lower than the glutathione synthase Michaelis constant (K m ) for glycine [ 96 ].…”
Section: Physiological Roles and Functions Of Dispensable Amino Acids...mentioning
confidence: 66%
See 3 more Smart Citations
“…Thus, even the relatively high protein intake of 1.13 g/kg/d, supplying about 3 g glycine/d, coupled with glycine from biosynthesis, is unlikely to meet biological requirements for optimal function. In concordance, an IAAO study showed that glycine intakes less than 37 mg/kg/d result in increased phenylalanine oxidation among late gestation pregnant women [ 95 ] (see next section). Arguments for glycine supplementation have also been made based on the observation that tissue glycine levels are often lower than the glutathione synthase Michaelis constant (K m ) for glycine [ 96 ].…”
Section: Physiological Roles and Functions Of Dispensable Amino Acids...mentioning
confidence: 66%
“…Yet, swine studies showed greater demand during pregnancy for the two dispensable amino acids glutamine and arginine, suggesting they were conditionally essential [ 130 ]. Rasmussen et al [ 95 ], tested glycine, a dispensable amino acid, using IAAO in the pregnant population during mid- and late gestation. During mid-gestation (~26 wks), a glycine-restricted diet did not affect whole-body protein synthesis, suggesting de novo glycine synthesis from interconversion of other amino acids such as serine was adequate for the maternal needs [ 95 ].…”
Section: New Estimates For Individual Amino Acid Requirements For The...mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, normalizing plasma glycine concentrations improves insulin sensitivity and thus, simple interventions such as dietary glycine supplementation may prove effective, although it is yet to be experimentally determined. Related to this is the fact that the simplest of amino acids from a structural point, glycine – a dispensable amino acid, has been shown to be a conditionally indispensable amino acid in infants in the past, and most recently in healthy pregnant women in later stages of pregnancy [9]. Thus, it is likely that in disease there is a dietary requirement for glycine and needs to be quantitatively confirmed in future.…”
mentioning
confidence: 99%